THE ROLE OF HUMAN CAPITAL IN STIMULATING ECONOMIC GROWTH IN THE REGIONS - Artikov Zokir Sayfiddinovich; Yusupov Jalil Normurod o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, we explore the key role of human capital in economic growth. Human capital, which includes the knowledge, skills and abilities of people, has become a decisive factor influencing regional development. We explore a variety of theoretical frameworks and empirical evidence, this research reveals the many ways in which investments in education, training, health and workforce development lead to increased productivity, innovation and external competitiveness. It also discusses the implications of policies and strategies to optimize the use of human capital for sustainable development in different regions.